2020
DOI: 10.1111/1346-8138.15293
|View full text |Cite
|
Sign up to set email alerts
|

Real life experience of apremilast in psoriasis and arthritis psoriatic patients: Preliminary results on metabolic biomarkers

Abstract: Psoriasis is a common inflammatory skin condition, affecting 2-4% of the worldwide population. Psoriasis remains an important public health challenge because there are many clinical forms of psoriasis in particular sites, probably related to the dysregulation of different cytokines. Therefore, there is a continuous need to improve treatment options with mechanisms of action different from those of the currently known therapies. Advances in knowledge of the molecular bases of pathogenesis lead to a better under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 24 publications
1
30
2
Order By: Relevance
“…An interesting study conducted by Mazzilli and coworkers observed a better therapeutic response to apremilast in diabetic patients compared to non-diabetic patients, with a reduction in blood glucose and total-and LDLc levels (94). Based on these findings, apremilast may be an appropriate therapeutic choice in patients with PsO/PsA and MetS (94).…”
Section: Apremilastmentioning
confidence: 94%
See 1 more Smart Citation
“…An interesting study conducted by Mazzilli and coworkers observed a better therapeutic response to apremilast in diabetic patients compared to non-diabetic patients, with a reduction in blood glucose and total-and LDLc levels (94). Based on these findings, apremilast may be an appropriate therapeutic choice in patients with PsO/PsA and MetS (94).…”
Section: Apremilastmentioning
confidence: 94%
“…Apremilast also appears to contribute to counteracting endothelial dysfunction, thus reducing CV risk (91,92), and to stabilize atherosclerotic plaques, hence blocking its evolution to an unstable, high risk phenotype (93). An interesting study conducted by Mazzilli and coworkers observed a better therapeutic response to apremilast in diabetic patients compared to non-diabetic patients, with a reduction in blood glucose and total-and LDLc levels (94). Based on these findings, apremilast may be an appropriate therapeutic choice in patients with PsO/PsA and MetS (94).…”
Section: Apremilastmentioning
confidence: 99%
“… 36 , 37 In a study by Mazzilli et al published in 2020, the authors confirmed the efficacy and safety of apremilast in favoring the improvement of skin and joint disease as well as the modulation of metabolic biomarkers in diabetic and non-diabetic psoriatic patients, and concluded that apremilast could be used successfully in psoriatic patients affected by cardiometabolic comorbidities, ensuring an improvement in both diseases. 38 …”
Section: Use Of Apremilast For Plaque Psoriasis In Special Populationsmentioning
confidence: 99%
“…109 As other PDE4 inhibitors, APR showed generally an acceptable safety profile. 110 The most common reported AEs were diarrhea, nausea, headache, and URTI. The gastrointestinal side-effects generally occurred within the first month of treatment and subsequently subsided.…”
Section: Targeted Synthetic Dmardsmentioning
confidence: 99%